Pengaruh Disiplin Kerja, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan di PT. Enseval Putera Megatrading Cabang Malang - Akhdan Bimantoro Santoso; Ike Kusdyah; Tri Wahyuni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the influence of work discipline, work motivation, and job satisfaction on employee performance at PT. Enseval Putera Megatrading Malang Branch. Human resources are a strategic asset that plays an important role in achieving organizational goals. Optimal employee performance cannot be separated from the level of work discipline, motivation, and job satisfaction experienced by employees in carrying out their duties. This research uses a quantitative approach with a survey method. The population consists of all permanent employees of PT. Enseval Putera Megatrading Malang Branch, with a census sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. The data were analyzed using multiple linear regression with the help of SPSS software. The results indicate that work discipline, work motivation, and job satisfaction partially and simultaneously have a positive and significant effect on employee performance. Work discipline improves compliance with company regulations, work motivation encourages enthusiasm and productivity, while job satisfaction creates comfort and loyalty toward the organization. These three variables together contribute to improving the quality of employee performance at PT. Enseval Putera Megatrading Malang Branch. This study is expected to provide practical contributions for the company in formulating human resource management policies oriented toward improving employee performance through strengthening work discipline, motivation, and job satisfaction. Furthermore, the findings may serve as a reference for future research in the field of human resource management.